Microtubule-dependent mitochondria alignment regulates calcium release in response to nanomechanical stimulus in heart myocytes - Miragoli,M; Sanchez,Alonso JL; Bhargava,A; Wright,PT; Sikkel,M; Schobesberger,S; Diakonov,I; Novak,P; Castaldi,A; Cattaneo,P; Lyon,AR; Lab,MJ; et al. (Cell Reports, 2015)
Arrhythmogenesis during heart failure is a major clinical problem. Regional electrical gradients produce arrhythmias, and cellular ionic transmembrane gradients are its originators. We investigated whether the nanoscale mechanosensitive properties of cardiomyocytes from failing hearts have a bearing upon the initiation of abnormal electrical activity. Hydrojets through a nanopipette indent specific locations on the sarcolemma and initiate intracellular calcium release in both healthy and heart failure cardiomyocytes, as well as in human failing cardiomyocytes. In healthy cells, calcium is locally confined, whereas in failing cardiomyocytes, calcium propagates. Heart failure progressively stiffens the membrane and displaces sub-sarcolemmal mitochondria. Colchicine in healthy cells mimics the failing condition by stiffening the cells, disrupting microtubules, shifting mitochondria, and causing calcium release. Uncoupling the mitochondrial proton gradient abolished calcium initiation in both failing and colchicine-treated cells. We propose the disruption of microtubule-dependent mitochondrial mechanosensor microdomains as a mechanism for abnormal calcium release in failing heart.